The rape of Nanking the forgotten Holocaust of World War II - Chang, Iris 1968-2004 (Penguin Books, 1998)
Relates an account of the 1937 massacre of 250,000 Chinese civilians in Nanking by the invading Japanese military, a carnage for which the Japanese government has never admitted responsibility.. - NjBwBT